Analisis Penurunan Tanah Jalan R.E. Martadinata Jakarta Utara Menggunakan Metode Konvensional dan Pengamatan GPS Geodetic - Ramadhan, Kurniawan; Syaiful; Taqwa, Fadhila Muhammad Libasut (Journal of Applied Civil Engineering and Infrastructure Technology, 2023)
Land subsidence in the areas of Pademangan, Ancol, Penjaringan, Cengkareng, Tanjung Priok, Cilincing, and Pulogadung is still ongoing. The land subsidence is influenced by the condition of the groundwater table and the effect of consolidation. The purpose of this research is to know the result of soil subsidence/ consolidation using conventional calculation methods and geodetic GPS observations on R.E. Martadinata Street on Bore Hole 3 with Point BM.CP.1 and Bore Hole 6 with Point BM.DKI.11 and to find out the results of the comparison of subsidence/ consolidation analysis methods between conventional calculations and geodetic GPS observations. The amount of soil subsidence/ consolidation with conventional calculation methods at Bore Hole 3 with Point BM CP.1 obtained 8.5 cm with a period of 2.3 years and at Bore Hole 6 with Point BM DKI.11 obtained 5.6 cm with a period of 0.4 years. The amount of soil subsidence/ consolidation with GPS Geodetic observations BM CP.1 point was obtained at 16.8 cm with a period of 3 years and at the DKI.11 BM Point obtained 17.5 cm with a period of 3 years. The results of soil subsidence/consolidation calculations using conventional calculation methods and GPS Geodetic observations there was a difference or deviation in Bore Hole 3 with Point BM CP.1 obtained 8.3 cm with a period of 0.68 years and in Bore Hole 6 with Point BM DKI.11 obtained 11.9 cm with a period of 2.64 years.